Impacts of Thai-Laos Cross-Border Tourism on Employment: The Case of Mukdahan Province, Thailand - SOMSWASDI, Chintana; CHANCHARAT, Surachai (Journal of Advanced Research in Law and Economics; Vol 6 No 4 (2015): JARLE Volume VI, Issue 4(14), Winter 2015, 2017)
The tourism industry is an economic unit important to Thailand's economy. The tourist expenditure generated incomes to the host economy. This paper aimed to study types of expenditures and the amount of money spent by tourists in Mukdahan Province, Thailand. This study also examined the impact of Mukdahan tourism industry on employment by analyzing the expense data obtained from tourist interviewees who visited attractive tourist attractions in this province between May and June, 2015 by adopting an Input-Output Model. The study revealed that the total expenses during the visiting could be separated into six categories. The highest amount of expenses was on accommodation, followed by food and beverage, others, goods and souvenir, service fees, recreation activities, and traveling expenses. Moreover, the spending of tourists could generate jobs for over 95,138 persons in Mukdahan Province in the service sector, followed by the agricultural sector and the industry sector.